2019
DOI: 10.1371/journal.ppat.1007841
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation from a Type I restriction modification system influences gene expression and virulence in Streptococcus pyogenes

Abstract: DNA methylation is pervasive across all domains of life. In bacteria, the presence of N6-methyladenosine (m6A) has been detected among diverse species, yet the contribution of m6A to the regulation of gene expression is unclear in many organisms. Here we investigated the impact of DNA methylation on gene expression and virulence within the human pathogen Streptococcus pyogenes , or Group A Streptococcus. Single Molecule Real-Time sequencing and subsequent methylation analysis identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 85 publications
4
41
1
Order By: Relevance
“…A previous study reported that deletion of the hsdRSM locus in an M28 GAS strain resulted in reduced transcription of mga , which encodes a positive regulator of genes encoding several virulence factors including M protein ( emm28 ) and C5a peptidase ( scpA ) [ 2 ]. To determine the impact of hsdM deletion on the transcript abundance of key virulence factors in the M1 strain 854, we used qRT-PCR to compare relative expression of genes encoding nine virulence factors in 854 wild type and 854Δ hsdM mutant cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that deletion of the hsdRSM locus in an M28 GAS strain resulted in reduced transcription of mga , which encodes a positive regulator of genes encoding several virulence factors including M protein ( emm28 ) and C5a peptidase ( scpA ) [ 2 ]. To determine the impact of hsdM deletion on the transcript abundance of key virulence factors in the M1 strain 854, we used qRT-PCR to compare relative expression of genes encoding nine virulence factors in 854 wild type and 854Δ hsdM mutant cells.…”
Section: Resultsmentioning
confidence: 99%
“…A global analysis of transcript levels in the hsdM deletion strain revealed no significant changes in expression of other genes compared to wild type. A previous study in an M28 strain found that deletion of the entire hsdRSM locus was associated with reduced expression of mga and Mga-regulated genes [ 2 ]. That we did not detect changes in transcription of these or other genes may reflect strain- or serotype-specific differences or effects of deleting hsdM alone in contrast to the entire hsd locus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general observation that DNA methylation, particularly that mediated by orphan methyltransferases (such as Dam or CcrM, which may themselves have evolved from RMSs), could alter transcription (44,48,84), led to the discovery of a broad suite of associated roles in DNA metabolism, cell physiology, and virulence (12,51,55,(85)(86)(87). An active research community continues to describe and characterize the additional roles that DNA methylation (from both restriction and orphan systems) play in bacteria (4,39,88), some of which can be very specific (67,69). We now show that, in contrast with expectations from this literature, the archetypal EcoKI Type I RMS has nearly zero impact on gene regulation or any phenotype among more than 1000 growth conditions tested.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that inactivation of the Hsd system in GAS is associated with increased transformation efficiency [2,3]. One study done in an M28 strain found that deletion of the three components of the Hsd system was associated with increased transformation efficiency [2]. Another study characterized a group of emm1 clinical isolates associated with invasive infections.…”
Section: Introductionmentioning
confidence: 99%